Efferent connections of the parvalbumin‐positive (PV1) nucleus in the lateral hypothalamus of rodents. Issue 14 (25th July 2013) - Celio, Marco R.; Babalian, Alexandre; Ha, Quan Hue; Eichenberger, Simone; Clément, Laurence; Marti, Christiane; Saper, Clifford B.
ABSTRACT A solitary cluster of parvalbumin‐positive neurons – the PV1 nucleus – has been observed in the lateral hypothalamus of rodents. In the present study, we mapped the efferent connections of the PV1 nucleus using nonspecific antero‐ and retrograde tracers in rats, and chemoselective, Cre‐dependent viral constructs in parvalbumin‐Cre mice. In both species, the PV1 nucleus was found to project mainly to the periaqueductal grey matter (PAG), predominantly ipsilaterally. Indirectly in rats and directly in mice, a discrete, longitudinally oriented cylindrical column of terminal fields (PV1‐CTF) was identified ventrolateral to the aqueduct on the edge of the PAG. The PV1‐CTF is particularly dense in the rostral portion, which is located in the supraoculomotor nucleus (Su3). It is spatially interrupted over a short stretch at the level of the trochlear nucleus and abuts caudally on a second parvalbumin‐positive (PV2) nucleus. The rostral and the caudal portions of the PV1‐CTF consist of axonal endings, which stem from neurons scattered throughout the PV1 nucleus. Topographically, the longitudinal orientation of the PV1‐CTF accords with that of the likewise longitudinally oriented functional modules of the PAG, but overlaps none of them. Minor terminal fields were identified in a crescentic column of the lateral PAG, as well as in the Edinger–Westphal, the lateral habenular, and the laterodorsal tegmental nuclei. So far, no obvious functions have been attributed to this small, circumscribed column ventrolateral to the aqueduct, the prime target of the PV1 nucleus. J. Comp. Neurol. 521:3133–3153, 2013. © 2013 Wiley Periodicals, Inc.